The Role of Sharia Insurance in Providing Islamic Financial Protection to the MSME Sector in Medan City - Rizkika Zalza Bila Utami; Sugianto; Atika (LP2M IAIN Palopo, 2025)
This study aims to examine the role of sharia insurance in providing financial protection in accordance with Islamic principles for the MSME sector in Medan City. The main focus of this study is to understand the level of awareness, understanding, and adoption of sharia insurance products among MSME actors. In addition, this study also explores various factors that influence the decision of MSME actors in choosing sharia insurance products and explains how the benefits offered can support the sustainability of their businesses. Thus, this study is expected to provide a significant contribution to the development of the sharia insurance sector in Indonesia, especially in Medan City, as well as providing insight to stakeholders regarding the importance of sharia insurance for the sustainability of MSMEs